FUTURE DEHUMANIZATION IN SOPHIA BANKS’ SHORT FILM UNREGISTERED: STUDY OF GOTTLIEB’S DYSTOPIAN LITERATURE - Putra, Natanael Ricky (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study aims to reveal forms of dehumanization in Unregistered, a short film by Sophia Banks, through a dystopian literary approach. The film portrays a future society governed by a totalitarian system enforcing a strict one-child policy, rendering second-born children illegal. Using a qualitative method with descriptive analysis, this research applies Erika Gottlieb’s dystopian theory. Findings indicate that Unregistered reflects key dystopian traits described by Gottlieb, or a universe of terror and trial. First, identity erasure is evident through the arrest of undocumented individuals. Second, perceptual manipulation emerges via technology, shown in Emily’s life, which depends on visual data recorded by Ata. Third, emotional and individual erasure is represented by Emily’s identity being substituted by Ata to maintain her existence. Fourth, mental control and historical erasure are illustrated by Emily’s disappearance and the subsequent denial of her existence. The film highlights a modern crisis where science and state policy become instruments of control that strip away humanity. Thus, Unregistered serves as speculative fiction and political allegory, critiquing power relations and ethical collapse in modern society.